2020
DOI: 10.1126/scitranslmed.aay5067
|View full text |Cite
|
Sign up to set email alerts
|

A decision algorithm to promote outpatient antimicrobial stewardship for uncomplicated urinary tract infection

Abstract: Antibiotic resistance is a major cause of treatment failure and leads to increased use of broad-spectrum agents, which begets further resistance. This vicious cycle is epitomized by uncomplicated urinary tract infection (UTI), which affects one in two women during their life and is associated with increasing antibiotic resistance and high rates of prescription for broad-spectrum second-line agents. To address this, we developed machine learning models to predict antibiotic susceptibility using electronic healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 33 publications
(36 reference statements)
2
95
0
2
Order By: Relevance
“…Low ESR1 expression in adipose tissue has been related to adiposity in humans 43 and studies in rodents show that AT depletion of ESR1 leads to mitochondrial dysfunction, adipocyte hypertrophy and IR 29 , 43 , 44 . In this study, we found no differences in expression of ESR1 across menopausal status in either SAT or VAT indicating that it is not a differential expression of ESR1 per se that drives the menopausal differences in AT phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Low ESR1 expression in adipose tissue has been related to adiposity in humans 43 and studies in rodents show that AT depletion of ESR1 leads to mitochondrial dysfunction, adipocyte hypertrophy and IR 29 , 43 , 44 . In this study, we found no differences in expression of ESR1 across menopausal status in either SAT or VAT indicating that it is not a differential expression of ESR1 per se that drives the menopausal differences in AT phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 3629 patients presenting between 2014 and 2016, the algorithm achieved a 67% reduction in the use of second-line antibiotics and reduced inappropriate antibiotic therapy by 18% relative to clinicians. 38 Further randomized trials are necessary to evaluate the utility of machine learning algorithms in antibiotic stewardship, followed by implementation science to disseminate the research findings into clinical practice.…”
Section: Rapid Diagnostic Testingmentioning
confidence: 99%
“…요로감염은 호흡기 감염 다음으로 사람에게 가장 흔한 감염병 중 하나이며 지역사회에서 흔하게 발생하는 감염질 환이다 [1]. 여성의 경우 40-50%에서 일생 동안 최소 한번 은 요로감염을 경험하는 것으로 알려져 있으며 그 중 상당 수는 반복적으로 감염된다 [2]. 이러한 요로감염은 높은 유 병율과 이환율로 항균제 사용의 빈도가 매우 높은 실정이 며 [3]…”
Section: Introductionunclassified